A20 inhibition of STAT1 expression in myeloid cells: a novel endogenous regulatory mechanism preventing development of enthesitis. Issue 3 (22nd August 2016) - De Wilde, Katelijne; Martens, Arne; Lambrecht, Stijn; Jacques, Peggy; Drennan, Michael B; Debusschere, Karlijn; Govindarajan, Srinath; Coudenys, Julie; Verheugen, Eveline; Windels, Fien; Catrysse, Leen; Lories, Rik; et al.
Abstract : Objectives: A20 is an important endogenous regulator of inflammation. Single nucleotide polymorphisms in A20 have been associated with various immune-mediated inflammatory diseases, and cell-specific deletion of A20 results in diverse inflammatory phenotypes. Our goal was to delineate the underlying mechanisms of joint inflammation in myeloid-specific A20-deficient mice (A20 myelKO mice). Methods: Inflammation in A20 myelKO mice was assessed in a time-dependent manner. Western blot analysis and quantitative PCR analysis were performed on bone marrow-derived macrophages from A20 myelKO and littermate control mice to study the effect of A20 on STAT1/STAT3 expression and STAT1/STAT3-dependent gene transcription in myeloid cells. The in vivo role of Janus kinase-Signal Transducer and Activator of Transcription (JAK-STAT) signalling in the development of enthesitis in A20 myelKO mice was assessed following administration of a JAK inhibitor versus placebo control. Results: Enthesitis was found to be an early inflammatory lesion in A20 myelKO mice. A20 negatively modulated STAT1-dependent, but generally not STAT3-dependent gene transcription in myeloid cells by suppressing STAT1 but not STAT3 expression, both in unstimulated conditions and after interferon-γ or interleukin-6 stimulation. The increase in STAT1 gene transcription in the absence of A20 was shown to be JAK-STAT-dependent. Moreover, JAK inhibition in vivo resulted in significant reduction of enthesitis, both clinically and histopathologically. Conclusions: Our data reveal an important and novel interplay between myeloid cells and tissue resident cells at entheseal sites that is regulated by A20. In the absence of A20, STAT1 but not STAT3 expression is enhanced leading to STAT1-dependent inflammation. Therefore, A20 acts as a novel endogenous regulator of STAT1 that prevents onset of enthesitis.